Response of Rice (Oryza sativa L.) to Sowing Dates, Nutrient and Weed Management - Longkumer, L. Tongpang; Singh, P. L. (International Journal of Bio-resource and Stress Management, 2023)
Studies on response of rice (Oryza sativa L.) to sowing dates, nutrient and weed management was carried out at the experimental farm of School of Agricultural Sciences and Rural Development, Nagaland University, Medziphema Campus during kharif seasons of 2004 and 2005. Sowing of rice right after the onset of monsoon showed better performance in terms of higher plant dry matter accumulation, yield attributes and yield of upland rice as compared to early sowing. 75% NPK (recommended) along with Azospirillum and Phosphotika recorded significantly the highest plant dry matter accumulation, grain and straw yield of rice. Butachlor @ 1.5 kg ha-1. (PE) significantly recorded the lowest weed density and weed dry weight, highest number of panicles, panicle length, grain and straw yield of rice.